Immunogenetics: Genome-Wide Association of Non-Progressive HIV and Viral Load Control: HLA Genes and Beyond - Limou, Sophie; Zagury, Jean Francois (Frontiers in Immunology, 2013)
Very early after the identification of the human immunodeficiency virus (HIV), host genetics factors were anticipated to play a role in viral control and disease progression. As early as the mid-1990’s, candidate gene studies demonstrated a central role for the chemokine co-receptor/ligand (e.g. CCR5) and Human Leukocyte Antigen (HLA) systems. In the last decade, the advent of genome-wide arrays opened a new era for unbiased genetic exploration of the genome and brought big expectations for the identification of new unexpected genes and pathways involved in HIV/AIDS. More than fifteen genome-wide association studies (GWAS) targeting various HIV-linked phenotypes have been published since 2007. Surprisingly, only the two HIV-chemokine co-receptors and HLA loci have exhibited consistent and reproducible statistically significant genetic associations. In this chapter, we will review the findings from the genome-wide studies focusing especially on non-progressive and HIV control phenotypes, and discuss the current perspectives.